EFFECT OF WEIGHT OF OTTER BOARDS ON THE HORIZONTAL OPENING FOR TRAWL NETS - PILLAI, N SUBRAMONIA; . VIJAYAN, V. VIJAYAN; NAYAR, S GOPALAN (Fishery Technology, 2016)
The paper gives briefly the experiments carried out to determinethe optimum wcig11t of otter board that should b::: used for atrawlgeaJ for better efficiency